The effect of Pandanus conoideus Lam. oil on pancreatic (i-cells and glibenclamide hypoglycemic effect of diabetic Wistar rats - Maliyah Madiyan, Nur Anisah, Winarto (Universitas Gadjah Mada, 2009)
Background: Oxidative stress has been implicated in pathogenesis and progression of many degenerative disorders including naturally occuring and chemically-induced diabetes mellitus. In addition to the increased production of free radicals, antioxidant defense systems are disturbed in diabetes mellitus. As a result, oxidative stress may cause oxidative damage of cellular, including Ii-cells of pancreas. Objective: This study was aimed at investigating the effect of P. eonoideus Lam. on hypoglycemic activity of glibenclamide and histochemical changes in pancreatic islets. Methods: Thirty male Rattus norvegicus rats were used in the study, and randomly selected. The animals were divided into two groups, each group consisted of 15 rats. Each group was devided into 3 subgroups, the first subgroups were subgroup 1; 2, 3 and the second was subgroup 4, 5, 6. Streptozotocin was injected intraperitoneally at a single dose of 60 mg/kg for induction of diabetes in the second group. Subgroup 1 and 4 did not receive anything, subgroup 2 and 5 received glibenclamide 0.09 g/kgBW/day and subgroup 3 and 6 received P. eonoideus Lam. 0.3 mLlkgBW/day and glibenclamide 0.09 g/kgBW/day. Rats were given P. eonoideus Lam. and glibenclamide everyday for 14 days. Hypoglycemic activity was evaluated in overnight fasted at day 1, 7 and 14, and the acute hypoglycemic activity was evaluated at time 0, 1, 2, 4, and 6 hour aher treatment at day 14. Blood was collected from orbital sinuses. Blood glucose level was determined using GOD-PAP method. At 15 day rat were killed, the pancreas was removed. The data was compared statistically using one-way analysis of variance (AN OVA) followed by post-hoc test and student unpaired t-test. For the analysis of immunohistochemical data, a non parametric test (Kruskal-Wallis) was used. Results: The combination of P. eonoideus Lam. and glibenclamide produced significant reduction in blood glucose in the serial study at day 1, 7 and 14 and comparable with that of standard drug, glibenclamide also control groups in normal and diabetic rats. It also produced significant reduction of blood glucose in the serial study at time 0, 1, 2, 4, and 6 hour after treatment at day 14. Significant increasing histoscore, number and diameter of Langerhans islets were observed in P. eonoideus Lam. treated rats. Conclusion: P. eonoideus Lam. could increase hypoglycemic effect of glibenclamide and histoscore, number, and diameter of Langerhans islets in diabetic rats. Key words: minyak buah merah - pancreas B-cells - glibenclamide hypoglycemic effect - diabetes